POLICY EVALUATION OF THE ZONATION SYSTEM IN ADMISSION OF NEW STUDENTS (Case Study of State Senior High School 2 Bandung) - Diki Suherman; Mohamad Ichsana Nur (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
This study aims to evaluate the Zoning System policy in the admission of new students listed in Permendikbud no. 17 of 2017, the purpose of the zoning system is to equal access to education in each district / city. however, in its implementation, it has not been able to eliminate the mindset of favorite and not favorite schools because the accreditation of several schools has not yet been evenly distributed, besides that, they still have to adapt to the implementation of this policy, one of which is at State Senior High School 2 Bandung which is the first cluster school before the zoning system for the admission of new students. This study uses a William N Dunn model of public policy evaluation with the CIPP approach (Context, Input, Process, Product). The research method uses descriptive research methods with a qualitative approach. Data collection techniques through interviews, observation and documentation study. The results showed that the application of the zoning system in the admission of New Students at State Senior High School 2 Bandung has been going very well but still needs new patterns in learning and the impact of implementing zoning system policies including improving the quality of learning, division of study groups, characteristics of students and the learning process at StateSenior High School 2 Bandung.